The Value Relevance of Fair Value Levels: Time Trends under IFRS and U.S. GAAP. (4th May 2021) - Filip, Andrei; Hammami, Ahmad; Huang, Zhongwei; Jeny, Anne; Magnan, Michel; Moldovan, Rucsandra
ABSTRACT: The IASB's post-implementation review of IFRS 13 Fair Value Measurement motivates our analysis of the evolution of the value relevance of fair value (FV) levels over time on banks that report under IFRS and U.S. GAAP. For both sets of standards, results provide evidence that is consistent with (1) an increase in value relevance across all three FV levels over time, and (2) a convergence of the value relevance of the three FV levels over time. However, FV levels exhibit systematically higher value relevance under U.S. GAAP compared to IFRS. Such gap has closed to some extent since the enactment of IFRS 13. This evolution is likely due to learning about FV accounting and changes in financial reporting regulations that increased disclosure requirements. These findings confirm the IASB's conclusions that FV levels' disclosure is useful to users of financial statements, but also emphasizes preparers and investors' learning over time.